Pengaruh Pendapatan Terhadap Tingkat Kesejahteraan Petambak Garam Di Desa Arungkeke Kabupaten Jeneponto - Nur Aisyah Qadri Saiful (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Prosperity is something that is hoped for by all levels of society because community or household inequality can be interpreted as a poor community or household. One important factor of welfare is income. The aim to be achieved in this research is to determine whether income has a positive effect on the level of welfare of salt farmer households in Arungkeke village, Arungkeke subdistrict, Jeneponto regency. This research design method is a survey method using a qualitative and quantitative approach where the unit studied is salt farmers. The influence of income on the level of welfare has a positive effect. To achieve prosperity, one of the factors is income.